Digitalisasi Komunikasi Pemasaran UMKM: Studi Kasus UMKM Mores Store - Fikri Fariz Fadhilah (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the impact of digital platforms on business communication strategies at the Mores Store MSME in Bandung City. Employing a qualitative approach, the research utilizes survey methods and descriptive analysis. Data was collected through offline interviews, literature review, and online data searches. The findings reveal that Mores Store actively leverages social media and online platforms, with Instagram and Shopee being the primary channels for promotional activities. Product promotion is heavily reliant on social media and e-commerce, which serve as the main pillars of their business communication strategy. In formulating their communication approach, Mores Store incorporates digital media by integrating persuasive interpersonal marketing, advertising, product photography, and the management of visually appealing social media displays. Overall, the study concludes that the managers of Mores Store possess a strong understanding and a high level of adaptability to digitalization and technological advancements in the era of Society 5.0, enabling them to develop effective and innovative business communication strategies.